Stimulus Organism Response Perspective on Understanding Gen Z's Loyalty in Shopping on the TikTok Shop - Pasaribu, Romindo M; Simanjuntak, Juara; Purba, Juliansen; Sembiring, Robi; Matondang, Vinsensius (Universitas Pendidikan Nasional, 2023)
This study aims to identify and analyze the direct effect of integration channels on customer affective and cognitive experiences and customer loyalty, as well as an indirect relationship where affective and cognitive experiences mediate between integration channels and customer loyalty Gen Z. This research is quantitative. The population used was Generation Z in Medan City with a sample size of 253 respondents. Sampling was carried out using a non-probability sampling approach using purposive sampling. The results of this study are product integration and price and transactions have a significant effect on customer experience both affectively and cognitively. Integration of promotions and access to information does not significantly affect the customer's experience effectively and cognitively. Customer service integration significantly affects cognitive customer experience but does not affect effective customer experience. The integration of customer service fulfillment has a significant effect on the customer's affective experience and does not affect the cognitive customer experience. Meanwhile, affective and cognitive customer experiences significantly affect Gen Z customer loyalty. In an indirect relationship, affective and cognitive customer experiences can mediate between promotion integration and access to information on customer loyalty. Affective experience cannot mediate between customer service integration on Gen Z loyalty while cognitive customer experience can mediate. Cognitive customer experience cannot mediate between integration of order fulfillment and loyalty, while affective experience can mediate. This research contributes to the omnichannel marketing literature by providing new insights into the importance of affective and cognitive customer experiences in omnichannel shopping.